Semiconductor Optics in Photonic Crystal Structures - Meier, Torsten; Koch, Stephan W. (Photonic Crystals: Advances in Design, Fabrication, and Characterization)

Kultur und Kirche in NRW: Versuch einer Bestandsaufnahme - Schroeter-Wittke, Harald (Dis-Kurs: Kirche und Kultur. Beiträge zur Kulturbörse der Evangelischen Kirche im Rheinland am 5.11.2004)

Da : Zwischen - Performative Seelsorge auf dem ÖKT in Berlin. Beobachtungen zu: Der Waschplatz. Performative Installation von Ute Pinkert und Hanne Seitz - Schroeter-Wittke, Harald (Wege zum Menschen)

Dance on the Volcano. Kirchentag als Kult(o)ur - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/28/hsw3.htm)

Das Amen in der Musik - Schroeter-Wittke, Harald (Amen. Beten als Projekt)

Wer gibt hier den Tona an? Musik bei Kasualien - Schroeter-Wittke, Harald (Lernort Gemeinde)

Zum Verlust von Grenze in "Weggeküßt" von Angela Krauß - Müller, Inez (Grenzen und Grenzauflösungen)

Knowledge Management in Self-Organizing Systems - Fuchs, Christian (Journal of Knowledge Management Practice 5 (2004))

The Antagonistic Self-Organization of Modern Society - Fuchs, Christian (Studies in Political Economy 73 (2004))

Science as a Self-Organizing Meta-Information System. INTAS Project “Human Strategies in Complexity“-Research Paper - Fuchs, Christian

Textile Patterns and Their Epistemological Functions - Kraft, Kerstin

In situ Synchrotron SAXS/XRD Study on the Formation of Ordered Mesoscopic Hybrid Materials with Crystal-Like Walls - Morell, Jürgen; Teixeira, Cilaine V.; Cornelius, Maximilian; Rebbin, Vivian; Tiemann, Michael; Amenitsch, Heinz; Fröba, Michael; Lindén, Mika (Chemistry of Materials)
In situ Synchrotron SAXS/XRD Study on the Formation of Ordered Mesoscopic Hybrid Materials with Crystal-Like Walls...

Ätztechnik - Hilleringmann, Ulrich (Silizium-Halbleitertechnologie)
In der Halbleitertechnologie werden die Materialien Siliziumdioxid, Siliziumnitrid, Polysilizium, Silizium, Aluminium sowie Wolfram und Titan mit ihren jeweiligen Metallsiliziden geätzt. Die Ätztechnik dient dabei zum ganzflächigen Abtragen eines Materials oder zum Übertragen der Struktur des lithografisch erzeugten Lackmusters in die darunter liegende Schicht. Für diese Aufgabe bieten sich einerseits nasschemische Ätzlösungen an, zum anderen eignen sich speziell entwickelte Trockenätzverfahren zur geforderten präzisen Strukturübertragung vom Lack in das Material.

Imprint structured organic thin film transistors as driving circuit in single-use sensor applications - Hilleringmann, Ulrich; Pannemann, C. (Fifth International Symposium on Instrumentation and Control Technology)

Piezoresistive pressure sensors in CVD diamond for high-temperature applications - Otterbach, Ralf; Hilleringmann, Ulrich (Fifth International Symposium on Instrumentation and Control Technology)

Nonlinear optical properties of semiconductor quantum wells inside microcavities - Meier, Torsten; Sieh, C.; Koch, S.W.; Lee, Y.-S; Norris, T.B.; Jahnke, F.; Khitrova, G.; Gibbs , H.M. (Optical Microcavities)
Experimental results on the nonlinear optical properties of semiconductors are compared with microscopic calculations which include Coulomb many-body correlations at different levels. One aim of this chapter is to show that microscopic theories, which have been developed for bare semiconductor heterostructures, are also able to describe semiconductor microcavities very well. Therefore, there is no need to phenomenologically introduce polariton-polariton interactions and parametric scattering of cavity polaritons to describe microcavity experiments, but instead a fully microscopic theory based on a Fermionic electron-hole Hamiltonian can be used. The treatment of many-body correlations using the second-order Born approximation and the dynamics-controlled truncation scheme are introduced and analyzed for bare heterostructures. These approaches are able to successfully explain a number of important experimental results which originate from the dynamics of many-body correlations. Then measurements of the nonlinear optical properties of a quantum-well microcavity are described. In these experiments the spectrally- and temporally-resolved nonlinear optical response is studied in detail using a pump-probe geometry. In particular, the polarization and intensity dependencies of the spectral probe reflection changes and their temporal evolution are analyzed. The prominent features of these experiments are well accounted for by the microscopic many-body theory.

Gerd Nuschmann / Manfred L. Pirner: Werbung, Religion, Bildung. Kulturhermeneutische, theologische, medienpädagogische und religionspädagogische Perspektiven (Beiträge zur Medienpädagogik 8), Frankfurt/M. 2003 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

18. Sonntag nach Trinitatis. Eph 5,8b-14: Brüchige Orientierungen - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

9. Sonntag nach Trinitatis. Phil 3,7-11(12-14): Vergessen - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Vom Verschwinden eines Ortes als Utopie - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Bibel im kulturellen Gedächtnis (EKD-Broschüre Synode 2003) - Schroeter-Wittke, Harald (Junge Kirche)

13. Sonntag nach Trinitatis. 1. Joh 4,7-12: Die Schuld der Liebe - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien II/2)

Sprache VI. praktisch-theologisch - Schroeter-Wittke, Harald (Religion in Geschichte und Gegenwart)

Intakt und Ekstase - Schroeter-Wittke, Harald (Kein Tag ohne Sinn - Kirchenjahr.)

Fano resonances in metallic photonic crystals - Meier, Torsten; Giessen, H.; Linden, S.; Christ, A.; Kuhl, J.; Nau, D.; Thomas, P.; Koch, S.W. (Fano resonances in metallic photonic crystals)
We demonstrate that interference of optical excitations of regularly arranged metallic nanodots on a waveguide shows spectral signatures of Fano resonances. The reason is coupling of localized particle plasmons and waveguide modes with different electronic continua.

Onset of Dynamical Localization in a Semiconductor Superlattice - Meier, Torsten; Koch, M.; Ciulin, V.; Carter, S.G.; Sherwin, M.S.; Koch, S.W.; Zide, J.; Driscoll, D.; Gossard, A.C. (International Quantum Electronics Conference)
An excitonic blue-shift is observed when a GaAs/AlGaAs superlattice is irradiated with a strong THz field. This observation is compared with a microscopic calculation, and is consistent with the onset of dynamical localization.

Five-Wave-Mixing Spectroscopy of Ultrafast Electron Dynamics at a Si(001) Surface - Voelkmann, C.; Reichelt, Matthias; Meier, Torsten; Koch, S. W.; Höfer, U. (Physical Review Letters)
The optically induced electron dynamics at a Si(001) surface is studied using a five-wave-mixing setup which measures the diffracted second-harmonic intensity induced by three ultrashort (13 fs) laser pulses. Depending on the time ordering of the pulses, this technique is capable of monitoring the temporal evolution of photoexcited one- or two-photon coherences, or populations. For a particular pulse sequence, the experiments show a delayed rise and a decay of the diffracted signal intensity on time scales of 50 and 250 fs, respectively. This response can be described by optical Bloch equations by including rapid scattering of the photoexcited carriers in the D(down)band of Si(001).

Nonequilibrium gain in optically pumped GaInNAs laser structures - Thränhardt, A.; Becker, S.; Schlichenmaier, C.; Kuznetsova, I.; Meier, Torsten; Koch, S. W.; Hader, J.; Moloney, J. V.; Chow, W. W. (Applied Physics Letters)
A theory is presented which couples a dynamical laser model to a fully microscopic calculation of scattering effects. Calculations for two optically pumped GaInNAs laser structures show how this approach can be used to analyze nonequilibrium and dynamical laser properties over a wide range of system parameters.

Überlegungen zum poetischen Kompositionsverfahren in Christoph Peters' Prosaband "Kommen und gehen, machmal bleiben" - Müller, Inez (Studia Neophilologica)

Coherent sheaves on rational curves with simple double points and transversal intersections - Burban, Igor; Drozd, Yu. (Duke Mathematical Journal)

Indecomposables of the derived categories of certain associative algebras - Burban, Igor; Drozd, Yu. (Proceedings of the ICRA-X Conference, Toronto 2002)

Derived categories of coherent sheaves on rational singular curves - Burban, Igor (Representations of finite dimensional algebras and related topics in Lie theory and geometry)

Derived tameness of nodal algebras - Burban, Igor; Drozd, Yu. (J. Algebra)

Digitale Animationen in dokumentarischen Fernsehformaten - Adelmann, Ralf (Analog/Digital – Opposition oder Kontinuum. Zur Theorie und Geschichte einer Unterscheidung)

Computeranimation als televisuelle Evidenzproduktion - Adelmann, Ralf (Evidenz … das sieht man doch!)

Ist Frieden der neue Name für Entwicklung? Herausforderungen und Grenzen der Evaluation von Maßnahmen des Zivilen Friedensdienstes - Freitag, Christine (Die Evaluierung erwünschter und unerwünschter Wirkungen von Ziviler Konfliktbearbeitung)

Interkulturelle Kommunikationskompetenz als Ziel eines wissenschaftlichen Studiums? - Freitag, Christine (Bildungsmanagement und Schulentwicklung)

Die Bedeutung der (Allgemeinen) Didaktik für das Lehren und Lernen in virtuellen Räumen - Herzig, Bardo (Jahrbuch Medienpädagogik 4)

Integrative Medienbildung. Ein (semiotischer) Beitrag zu einer integrativen Medienbildungstheorie - Herzig, Bardo (Medienimpulse 48(2004))

Gestaltung von Unterricht. Eine Einführung in die Didaktik. - Tulodziecki, G.; Herzig, Bardo; Blömeke, S.

Mediendidaktik. Medienverwendung in Lehr- und Lernprozessen - Tulodziecki, G.; Herzig, Bardo

Medienpädagogische Kompetenz - Herzig, Bardo (Handbuch Lehrerbildung)

Reflexives Lernen mit digitalen Videos. Ein Beitrag zur didaktischen Bearbeitung des Theorie-Praxis-Verhältnisses in der Lehrerausbildung - Herzig, Bardo; Grafe, S.; Reinhold, P. (Nimm’ doch mal die Kamera! Zur Nutzung von Videos in der Lehrerausbildung – Beispiele und Empfehlungen aus den Naturwissenschaften)

Strategien und Handlungselemente für ein Disseminationskonzept des Modellversuchs SINUS-Transfer NRW - Herzig, Bardo; Grafe, S.

Unterrichtsreflexion mit digitalem Video im erziehungswissenschaftlichen (Lehramts-)Studium - Herzig, Bardo; Grafe, S. (Seminar Heft 3/04)

Neue Medien in der Bildung. Förderbereich Schule. Audit-Abschlussbericht - Herzig, Bardo

Der dunkle Kontinent. Rassenbegriffe und Kolonialpolitik im Deutschen Kaiserreich - Schubert, Michael (Rassenmischehen – Mischlinge – Rassentrennung. Zur Politik der Rasse im deutschen Kolonialreich)

Zwischen ‚Kulturmission’ und ‚Naturgewalt’. Bilder vom schwarzen Fremden in Deutschland von der Kolonialpublizistik der späten 1870er Jahre bis zur neuen Kolonialpolitik der ‚Ära Dernburg’ - Schubert, Michael (Integrationen des Widerläufigen. Ein Streifzug durch geistes- und kulturwissenschaftliche For-schungsfelder)

Wie wird Entwicklung gemacht? - Petra, Dannecker; Spiegel, Anna (IFF-Info : Zeitschrift des Interdisziplinären Zentrums für Frauen- und Geschlechterforschung)

Beyond Cultural Differences: 'Intercultural' Co-operation in a German/Sri Lankan Development Project - Knoll, Lisa (Internationales Asienforum)
As development co-operation is most of the time 'intercultural' co-operation, behaviour is frequently explained by cultural arguments. I argue that regarding behaviour as being generated by cultural origin precludes integration in a conglomerate of structural dependencies and formal and informal relationships. It is argued that culture is first of all a powerful and persuasive discourse in development co-operation and that it provides orientation in complex working situations. 'Hide-and-seek' and 'discussing openly' - behavioural patterns considered to be either typically Sri Lankan (Eastern) or typically German (Western) - are presented in order to show that culture is a reciprocal process of identity creation rather than a feasible explanation of behaviour. The structural integrations of project collaborators show that behaviour in a ' hide-and-seek' manner more likely reflects dependencies in a counterpart set-up than to cultural origin.